Old English Power Structure in the Warlike Nature in Riddles no. 3, no, 29, no. 50 from the Exeter Book - Herditya Wahyu Widodo (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This study focuses on Old English nature-themed riddle texts from the Exeter Book, analyzing the natural imageries that are significant in investigating how the literary content of Old English riddles, as accepted forms of poetry, reveals the Anglo-Saxon culture of their original authors. I focus on the power structure in Anglo-Saxon society revealed in the riddles, by analyzing the topic of warlike nature in them, focusing on the riddles no. 3, “Storm”, no. 29 “Sun and Moon,” and no. 50, “Fire.” Natural experience described in these riddles is rendered by the Anglo-Saxons to reflect power hierarchy between male and female, servant and master, and human with God. The Anglo-Saxon riddles identify and assign the potent warlike attributes and actions of nature, and assign them to the more powerful factions (God, Master, Male) over the weaker factions (Humans, Servants, Female). This is done by the authors as an acceptable cultural interpretation of these natural phenomena, put in the riddles to make it possible for the riddles’ intended Anglo-Saxon audience as clues to arrive at a culturally agreeable answer. Keywords: old English, old English riddles, natural imagery, old English poetry, war imagery Abstrak: Studi ini berfokus pada teks teka-teki (Riddles) Inggris Kuno (Old English) bertema alam dari the Exeter Book, dengan menganalisa imaji alam yang signifikan, untuk mengetahui bagaimana teka-teki Inggris Kuno, sebagai salah satu karya sastra berbentuk puisi, mengungkapkan budaya Anglo-Saxon dari penulis aslinya. Saya berfokus pada struktur kekuasaan (power structure) dalam masyarakat Anglo-Saxon yang terungkap dalam teks teka-teki, dengan menganalisis topik sifat suka perang di pada teka-teki no. 3, "Badai", no. 29 “Matahari dan Bulan,” dan no. 50, "Api." Pengalaman hidup mengenai alam digambarkan dalam teka-teki ini oleh para penulis Anglo-Saxon dengan mencerminkan hierarki kekuasaan antara laki-laki dan perempuan, hamba dan tuan, dan manusia dengan Tuhan. Teka-teki Anglo-Saxon mengidentifikasi dan menetapkan atribut dan tindakan alam yang suka berperang (warlike) kepada faksi yang lebih kuat (Dewa, Tuan, Laki-Laki) di atas faksi yang lebih lemah (Manusia, Pelayan, Wanita). Hal ini dilakukan oleh para penulis sebagai interpretasi budaya atas fenomena alam yang mereka lihat, dan dimasukkan ke dalam teka-teki untuk memungkinkan pembaca Anglo-Saxon sebagai petunjuk untuk sampai pada jawaban yang dapat diterima secara budaya. Kata kunci: old English, Inggris kuno, teka-teki Inggris kuno, imaji alam, puisi Inggris kuno, imaji perang